2012
DOI: 10.1111/j.1467-9299.2011.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Companies and Local Governance: No Man Can Serve Two Masters

Abstract: Abstract:This article looks at the use of institutionalized public-private partnership (PPP) arrangements by local governments for the delivery of different types of infrastructure. It starts by analysing the mixed company model from a theoretical point of view, in particular the potential for internal regulation and the achievement of a relational agreement. Then, after discussing the practicalities of crafting this type of governance structure, four Portuguese case-studies are examined. The empirical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 43 publications
1
82
0
2
Order By: Relevance
“…Simultaneously, the data corroborate the hypothesis that transaction costs and principal-agent problems induce a higher chance of failure (hypothesis 1a). This chance of failure increases under joint or mixed ownership (hypotheses 3a and 3b), which exacerbate transaction costs and principal-agent problems, and particularly the problem of serving multiple masters (Da Cruz and Marques 2012;Van Thiel 2016;Waterman and Meier 1998) is pressing and should be studied further. However, if these problems are overcome, cooperation with the private sector or between localities through a MOC can be very beneficial, as the data demonstrate (hypotheses 3a and 3b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneously, the data corroborate the hypothesis that transaction costs and principal-agent problems induce a higher chance of failure (hypothesis 1a). This chance of failure increases under joint or mixed ownership (hypotheses 3a and 3b), which exacerbate transaction costs and principal-agent problems, and particularly the problem of serving multiple masters (Da Cruz and Marques 2012;Van Thiel 2016;Waterman and Meier 1998) is pressing and should be studied further. However, if these problems are overcome, cooperation with the private sector or between localities through a MOC can be very beneficial, as the data demonstrate (hypotheses 3a and 3b).…”
Section: Discussionmentioning
confidence: 99%
“…Five studies, all large-N studies, find that mixed MOCs realise real efficiency gains (Bognetti and Robotti 2007;Filippini and Prioni 2003;Garrone, Grilli, and Rousseau 2013;Marra 2007;Pérez-López, Prior, and Zafra-Gómez 2015). Furthermore, three other studies, all small-N case studies, emphasise potential efficiency gains from mixed MOCs, but show that these could not come to long-term fruition due to goal conflict and negotiation problems (Da Cruz and Marques 2012;Marques and Berg 2011) or labour conflict (Swarts and Warner 2014). Only Roy and Yvrande-Billon (2007) (a large N-study) finds a negative effect of mixed MOCs in technical efficiency.…”
Section: Mixed Mocsmentioning
confidence: 96%
See 1 more Smart Citation
“…Do public administrators (often known as charter authorizers) award contracts even where there is insufficient competition and, if so, with what implications for corruption and the ability to effectively manage and, where necessary, to punish these schools when they know that their governmental supervisors cannot easily replace them (if at all)? While these questions are in need of answers-especially in reference to charter schools-one study examined a bidding process wherein private companies were sought as partners for school construction in Portugal (Da Cruz & Marques, 2012). Here, the Portuguese government worked with the only willing private sector partner and, in so doing, found that this company could not "serve two masters" in that it prioritized profit making over public sector needs (Da Cruz & Marques, 2012, p. 756).…”
Section: Theory Vs Reality In the Literaturementioning
confidence: 99%
“…The IT department is responsible for operating and supporting all necessary IT services for a SOE. Compared to other departments of SOEs, IT departments more likely face organizational transformations caused by increasing initiatives of public private partnerships in the IT sector (Sharma 2012;Da Cruz and Marques 2012), realization of IT outsourcing activities (Joha and Janssen 2010;Cordella and Willcocks 2012) or the upcoming trend of IT insourcing (Damanpour et al 2013;Warner and Hefetz 2012). With these issues in mind, our work addresses the following research question (RQ): new enterprise resource planning (ERP) systems and apply this framework in a case study with a German airport.…”
Section: Introductionmentioning
confidence: 99%